A Journey from the Beginning: creation accounts in the Book of Genesis - Ghosn, Margaret (Coventry Press, 2022)
"...An interpretation of God's purposes for us today - how, by exploring in detail the texts of the first three chapters of Genesis, we may discover their message and meaning; and how they direct us in our life choices.." -- Back cover